Pro Angular 9 : build powerful and dynamic web apps - Freeman, Adam, 1972- (Apress, 2020)
Welcome to this one-stop-shop for learning Angular 9. Pro Angular 9 is the most concise and comprehensive guide available, giving you the knowledge you need to take full advantage of this popular framework for building their own dynamic JavaScript applications. The fourth edition of this popular guide explains how to get the most from Angular 9, starting with an in-depth overview of the MVC pattern, presenting the range of benefits it can offer. From there, you will begin learning how to use Angular in your projects, starting with the nuts-and-bolts concepts, and progressing on to more advanced and sophisticated features. Each topic in this full-color book provides you with precisely enough learning and detail to be effective. In true Adam Freeman style, the most important features are given full court press treatment, while also addressing common problems and how to avoid them. What You Will Learn: Gain a solid architectural understanding of the MVC Pattern Create rich and dynamic web app clients using Angular 9 Use the ng tools to create and build an Angular project Extend and customize Angular Acquire stills to unit test your Angular projects This book is for web developers who want to create rich client-side applications and possess a foundational knowledge of HTML and JavaScript About the Author: Adam Freeman is an experienced IT professional who has held senior positions in a range of companies, most recently serving as chief technology officer and chief operating officer of a global bank. Now retired, he spends his time writing and long-distance running. "Adam's books provide a finely tuned blend of architectural overview, technical depth, and experience-born wisdom. His clear, concise writing style, coupled with project driven real world examples, make me comfortable recommending his books to a broad audience, ranging from developers working with a technology for the first time to seasoned professionals who need to learn a new skill quickly." Keith Dublin, S olution Principal, Slalom Consulting